Extraction technology of flavonoids from Angelica dahurica - Fei Fan; Ning Lu; Shunchang Pu; Zhien Ding (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT As a traditional Chinese medicine, Angelica dahurica has significant medicinal and nutritional value. To optimize the extraction of flavonoids from Angelica dahurica and enhance its medicinal value, this study was conducted to optimize the process using response surface methodology and investigated the effects of ultrasonication time, ethanol concentration, and solid-liquid ratio on the extraction rate of flavonoids in Angelica dahurica based on single-factor tests. The ultrasound-assisted extraction process can significantly improve the extraction rate of flavonoids in Angelica dahurica, and the flavonoids exhibit antioxidant capacities, which provides a practical basis for the extraction of active ingredients from Angelica dahurica.